Antibacterial Activity Test of Jatropha multifida L. sap against Staphylococcus aureus and Methicillin Resistant Staphylococcus aureus (MRSA) in vitro - Anastassya Yuniar Setyo Putri; Marijam Purwanta; DantiNur Indiastuti; Arthur Pohan Kawilarang (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Jatropha multifida L. is a plant that commonly used as a traditional treatment espesciallyfor wounds. It has been proven that its sap had an antibacterial activity against Staphylococcus aureus.Staphylococcus aureus has developed resistant strains named MRSA (Methicillin-Resistant Staphylococcusaureus). Due to this resistance development, hopefully the sap of Jatropha multifida L. can also performedits antibacterial activity against MRSA. Objective: To determine the antibacterial activity of the sap ofJatropha multifida L. against Staphylococcus aureus and MRSA. Methods: A well-diffusion method wasperformed on several concentration: 100%, 50%, 25%, 12.5%, and 6.25%. From this method, the diameterof the inhibition zone produced by the sap was measured. Results: The average of inhibition zone diameterwere 11.29 - 16.00 mm for Staphylococcus aureus and the bigger zone 12.15 - 17.61 mm for MRSA.Conclusion:Jatropha multifida L. had antibacterial activity against Staphylococcus aureus and MRSA. Thisplant showed higher antibacterial activity on MRSA than Staphylococcus aureus.